Tinjauan Literartur Hubungan Tingkat Pengetahuan Tentang SIM dengan Perilaku Safety Riding pada Remaja Pengendara Sepeda Motor Teori Health Belief Model (HBM) - Ratna Vanessa; Luqman Effendi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Introduction: Driving safety is very important to protect yourself and others from traffic accidents. Data shows that in, approximately 1.19 million people died in accidents. Due to high mobility needs, teenagers often violate regulations because they do not know how to drive. This study reviews the literature on the relationship between driver's license knowledge levels and safe driving behavior among teenagers. This research is a literature review of studies published in the last. Data sources were taken from the Google Scholar, PubMed, ProQuest, and Onesearch.id databases using the keywords compliance factors, traffic behavior, teenagers, and road safety. The inclusion criteria were open access journals in Indonesian and English.Results: Most studies showed a significant relationship between knowledge level and safe driving behavior or satisfaction, according to ten pieces of literature. Although most adolescents have good knowledge (up to 91% in one study), some adolescents are non-compliant. In addition to knowledge, other factors that influence driving behavior are attitudes and perceptions, the role of peers, and possession of a C driver's license.